Imag(in)ing Sardinia - Alù, Giorgia (Incontri. Rivista europea di studi italiani, 2014)
Review of: Maria Bonaria Urban, Sardinia on Screen. The Construction of the Sardinian Character in Italian Cinema, Amsterdam–New York, Rodopi, 579 p., 2013, ISBN: 9789042037502, € 120 / US$ 168; eBook: 9789401210010, € 108 / US$ 151.